The Effects of Physical Activity and Obesity on Hypertension in Adolescents: Meta-Analysis - Maria Imakulata Berek; Agus Kristiyanto; Vitri Widyaningsih (Journal of Health Promotion and Behavior, 2020)
Background: The incidence of hypertension is always increasing every year both in Indonesia and in the world. Adolescents with high blood pressure are more likely to become adults with hypertension if not treated immediately. This study aimed to review the effects of physical activity and obesity on hypertension in adolescents using meta-analysis.Subjects and Method: Meta-analysis was performed by searching for articles from the database, namely Pubmed, Science Direct, Springer Link and Google Scholar. The keywords used are "physical activity" AND "obesity" AND "hypertension" OR "high blood pressure" AND "adolescent" AND "cross-sectional". The inclusion criteria in this study were full-text articles with a cross-sectional design, in English, for the period of 2010-2020. Article analysis was using RevMan 5.3.Results: The total number of articles analyzed was 14 articles from Nigeria, Brazil, Gabon, Germany, Tunisia, Algeria, China, Egypt, Indonesia, Lithuania, Greece, and Ghana. The results of the meta-analysis showed that physical activity increased the incidence of hypertension in adolescents (aOR= 2.70; 95% CI= 1.81 to 4.04; p<0.001; I2= 87%). Obesity increased the incidence of hypertension in adolescents (aOR = 1.71; CI 95% = 1.34 –2.17; p < 0.001; I2 = 41%).Conclusion: Physical activity affects the incidence of hypertension in adolescents. Obesity affects the incidence of hypertension in adolescents.Keywords: hypertension, physical activity, obesity, adolescentsCorrespondence: Maria Imakulata Berek, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: imma123433@gmail.com. Mobile: 085311622368.Journal of Health Promotion and Behavior (2020), 05(04): 296-305https://doi.org/10.26911/thejhpb.2020.05.04.07.